METHOD OF CONDUCTING PRACTICAL CLASSES IN PHYSICS WITH STUDENTS OF PHYSICAL SPECIALTIES IN CREDIT-MODULAR SYSTEM OF ORGANIZATION OF EDUCATION - Yatsura, M.; Gamarnyk, A.; Rachiy, B. (Physical and Mathematical Education, 2021)
Problem formulation. The transition to a credit-module system of student education requires a significant improvement in all types of classes, including practical work, and hence the need to improve the methodology of improving the efficiency and intensification of practical classes, and increasing the role of independent work of students in this. This shows that the issue of modernization of methods of organization, preparation and conduct of practical classes in physics remains relevant. Materials and methods. The long-term experience of the authors in organizing and conducting practical classes in physics with students of physical specialties and analysis of pedagogical, psychological and scientific-methodical literature is used. Results. An innovative method of conducting practical classes in the general course of physics for students of physical specialties in higher education institutions is proposed. It is proposed to check the level of theoretical knowledge of students on this topic by testing, rather than by interviewing students, as is customary in the classical method. For this purpose, about 2,000 tests have been prepared, which allows testing in almost every section of the curriculum. The student must take the test before the start of the practical lesson. For conducting practical classes methodical materials are created, which are placed in EEMCO under the name "Materials for practical classes". Students have the opportunity to use them, both in preparation for practical classes and in their conduct. A new form of keeping a synopsis of the problems solved in practical classes and an explanation to them has been developed and proposed for use, which, in the opinion of the authors, is more rational than keeping a synopsis in an ordinary notebook. This form is more convenient to use and allows the student to accumulate a large number of solved problems by the end of the study, which will be useful in his further work. New forms of independent work on solving problems have been introduced - these are two independent home control works, which contain about 70 tasks, two sets of tasks (about 100 tasks in each) to prepare for classroom tests and so-called rating tasks, which are recommended for students to solve in order to increase their own rating during the semester. Conclusions. The method of conducting practical classes on the general course of physics (section Optics) for students of physical specialties in higher education institutions is offered.